2019
DOI: 10.1371/journal.pone.0221322
|View full text |Cite
|
Sign up to set email alerts
|

Family-based case-control study of exposure to household humidifier disinfectants and risk of idiopathic interstitial pneumonia

Abstract: Background In Korea, several household humidifier disinfectants (HDs) were clinically confirmed to cause HD-associated lung injury (HDLI). Polyhexamethylene guanidine (PHMG) phosphate is the main ingredient of the HDs found to be associated with lung disease. However, the association of HDs with other interstitial lung disease including idiopathic interstitial pneumonia (IIP) is not clear. We examined the relationship between HD exposure and IIP in a family-based study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Taken together, it seems plausible that HD-induced inflammation and mRNA expression of fibronectin might trigger a wound-healing response, causing epithelial cells to be stiff and thickened, eventually leading to pulmonary fibrosis, which is identical to the features of HDLI cases. Although a few small-scale studies of matched case-control design support the above experimental findings and suggest significant associations with HD exposure and an increased risk of HDLI, there were still limited large-scale epidemiological studies [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Taken together, it seems plausible that HD-induced inflammation and mRNA expression of fibronectin might trigger a wound-healing response, causing epithelial cells to be stiff and thickened, eventually leading to pulmonary fibrosis, which is identical to the features of HDLI cases. Although a few small-scale studies of matched case-control design support the above experimental findings and suggest significant associations with HD exposure and an increased risk of HDLI, there were still limited large-scale epidemiological studies [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 86%
“…A growing body of evidence from in vitro [ 9 , 10 ] and in vivo [ 11 , 12 ] studies demonstrated that exposure to PHMG, CMIT/MIT, and PGH chemicals causes apoptosis, inflammation, and reactive oxygen stress in alveolar epithelial cells and induces airway barrier injuries, thereby leading to pulmonary inflammation and lung fibrosis. In addition, matched case-control studies (i.e., hospital-based, family-based, and community-based case-control studies) reported consistent findings of significant associations between the levels of HD exposure and the risk of a fatal lung injury called HD-associated lung injury (HDLI) [ 13 , 14 , 15 ]. Despite the potential role of PHMG, CMIT/MIT, and PGH in the pathogenesis of fatal lung injury as well as emerging evidence from case-control studies, the nationwide contribution of exposure to HD-related synthetic chemicals to the lung injury epidemic remains underappreciated.…”
Section: Introductionmentioning
confidence: 99%
“…In human and animal studies, the inhalation of PHMG is strongly associated with lung injuries, including interstitial pneumonitis and lung fibrosis, which eventually lead to death owing to the loss of lung function [ 1 , 28 , 29 , 30 ]. Lung injuries occur in people exposed to PHMG, a representative HD substance; however, less severe lung damage has been reported in people exposed to CMIT [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Toxics 2022, 10, 371 2 of 12 review of epidemiologic studies has reported a causal association between HD exposure and the risk of HD-related lung injury (HDLI) [11]. Furthermore, a study of lung injury cases suggested a higher risk of lung injury in people associated with HD use than those with insecticide uses, indoor molds, and only humidifier uses (without HD) at home [12], and a previous study suggested that HD exposure was associated with lung diseases, including idiopathic interstitial pneumonia [13].…”
Section: Introductionmentioning
confidence: 99%